Targeting of EGFR and HER2 with therapeutic antibodies and siRNA : A comparative study in glioblastoma cells - Wichmann, Henri; Guettler, Antje; Bache, Matthias; Taubert, Helge; Rot, Swetlana; Kessler, Jacqueline; Eckert, Alexander W.; Kappler, Matthias; Vordermark, Dirk (Strahlentherapie und Onkologie, 2015)
The epidermal growth factor receptors, EGFR (HER1) and HER2, have proven prognostic relevance in a variety of human malignancies and both are functionally involved in the molecular pathogenesis of malignant gliomas.We selectively inhibited EGFR and HER2 in glioblastoma cell lines via EGFR- and HER2-specific siRNAs and through the binding of the therapeutic antibodies cetuximab and trastuzumab. The expression of EGFR and HER2 was verified by real-time PCR and western blot analyses. We examined the growth rate, cell cycle distribution, cell migration, clonogenic survival, and radiosensitivity of U251MG and LN-229 glioblastoma cell lines to determine the physiological and cell biological effects of EGFR and HER2 targeting.EGFR and HER2 targeting using the therapeutic antibodies cetuximab and trastuzumab had no effect on cellular growth rate, cell cycle distribution, cell migration, clonogenic survival, and radiosensitivity in the cell lines U251 and LN-229. In contrast, siRNA knock-down of EGFR and HER2, reduced the growth rate by 40-65 %. The knock-down of EGFR did not change the cell migration rate in the cell lines U251 and LN-229. However, knock-down of HER2 reduced the cell migration rate by 50 %. Radiobiological analysis revealed that EGFR knock-down induced no radiosensitization in U251MG and LN-229 cells. However, the knock-down of HER2 induced radiosensitization in U251MG cells.The epidermal growth factor receptor HER2 is a promising anti-tumor target for the therapy of glioblastoma. HER2 targeting may represent a promising strategy to induce cell physiological and radiobiological anti-tumor effects in glioblastoma.
EVALuna2:16310